Pelatihan Guru Matematika dalam Pembuatan Tes Formatif Berbasis Media E-Learning - Faradillah, Ayu; Hadi, Windia; Tsurayya, Ayu (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
The use of e-learning in learning is growing. However, limiting the use of gadgets in learning activities is one of the reasons from mathematics teachers do not use e-learning in the classroom so learning is beome less innovative and creative. There is even teacher who cannot use laptop because he/she have never known e-learning or provided used learning media. The method used in this service is the guided training method where all participants are guided from the beginning of the account creation to the introduction of tools, student’s and parent’s account which available at Edmodo. In this training activity, participants also had to produce output in the form of formative test questions in the form of shared quizzes at Edmodo. Before knowing Edmodo math teachers were doubtful about its use for formative tests. However, in the training process especially when knowing the unique way to write equations on Edmodo, the level of enthusiasm and the desire of teachers to apply in the classroom also increased. All participants felt that e-learning was able to help teachers create an innovative, creative classroom atmosphere and increase motivation to learn mathematics in class.